Kodokan Judo throwing techniques - S. Biron Ebell (Universidad de León, 2012)
<span style="mso-ansi-language: EN-US; mso-ascii-font-family: Calibri; mso-fareast-font-family: Calibri; mso-hansi-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; mso-bidi-font-weight: bold;" lang="EN-US">Toshiro Daigo. <span style="mso-ansi-language: EN-US; mso-ascii-font-family: Calibri; mso-fareast-font-family: Calibri; mso-hansi-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; mso-bidi-font-weight: bold;" lang="EN-US">Kodansha International, 2005. <span style="mso-ansi-language: EN-GB; mso-ascii-font-family: Calibri; mso-fareast-font-family: Calibri; mso-hansi-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; mso-bidi-font-weight: bold;" lang="EN-GB">288 páginas, 26x19 cm. I.S.B.N.: 4-7700-2330-8.